Evidence for differences in regioselective and stereoselective glucuronidation of silybin diastereomers from milk thistle (Silybum marianum) by human UDP-glucuronosyltransferases - Jančová, Petra; Siller, Michal; Anzenbacherová, Eva; Křen, Vladimír; Anzenbacher, Pavel; Simánek, Vilím (Xenobiotica; the fate of foreign compounds in biological systems, 2011)
The flavonolignan silybin, the main component of silymarin, extract from the seeds of Silybum marianum, is used mostly as a hepatoprotectant. Silybin is almost 1:1 mixture of two diastereomers A and B. The individual UDP-glucuronosyltransferases (UGTs) contributing to the metabolism of silybin diastereomers have not been identified yet. In this study, the contribution of UGTs to silybin metabolism was examined. The potential silybin metabolites were formed in vitro by incubating silybin (i) with the human liver microsomal fraction, (ii) with human hepatocytes and finally (iii) with 12 recombinant UGTs (UGT1A1, 1A3, 1A4, 1A6, 1A7, 1A8, 1A9, 1A10, 2B4, 2B7, 2B15 and 2B17). High-performance liquid chromatographic (HPLC) techniques with UV detection and additionally MS detection were used for metabolite identification. Hepatocytes and microsomes formed silybin A-7-O-β-D-glucuronides, B-7-O-β-D-glucuronides, A-20-O-β-D-glucuronides and B-20-O-β-D-glucuronides. With recombinant UGTs, the major role of the UGT1A1, 1A3, 1A8 and 1A10 enzymes but also of the UGT1A6, 1A7, 1A9, 2B7 and 2B15 in the stereoselective reactions leading to the respective silybin glucuronides was confirmed. UGT1A4, UGT2B4 and UGT2B17 did not participate in silybin glucuronidation. The predominant formation of 7-O-β-D-glucuronides and the preferential glucuronidation of silybin B diastereomer in vitro by human UGTs were confirmed.
Keywords: Microsomes, Liver; kultivované buňky; Hepatocytes; Silybum marianum; glukuronosyltransferasa; Stereoisomerism; rekombinantní proteiny; Silybin; mužské pohlaví; silymarin; Chromatography, High Pressure Liquid; Recombinant Proteins; glukuronidy; Glucuronosyltransferase; ostropestřec mariánský; vysokoúčinná kapalinová chromatografie; Silymarin; Cells, Cultured; hepatocyty; silibinin; stereoizomerie; ženské pohlaví; Humans; jaterní mikrozomy; Glucuronides; Female; lidé; Male